The effect of different combinations of vascular, dependency and cognitive endpoints on the sample size required to detect a treatment effect in trials of treatments to improve outcome after lacunar and non-lacunar ischaemic stroke - Makin, Stephen D.J.; Doubal, Fergus; Quinn, Terence J.; Bath, Philip M.W.; Dennis, Martin S.; Wardlaw, Joanna M. (SAGE, 2017)
Background